Trend of fatal poisoning in Kanpur: a two year autopsy based study - M. Awasthi, Puneet; Verma, Soni; Dev, Rahul; Bajpai, Anand (International Journal of Research in Medical Sciences, 2017)
Background: Kanpur is not only the biggest city of the Uttar Pradesh but also 9th most populated city of the India and is the main centre of commercial and industrial activities. Kanpur is situated at the bank of holy river Ganga. It is very crowded city and facing the problems of population influx from neighboring towns and villages. Apart from fame for industry, Kanpur lies between two rivers Ganga and Pandu. The land of Kanpur district is plain and fertile with Cultivable Barren Land 185480 Hectare. Kanpur is an only notified metropolitan area by UP Government under Code of Criminal Procedure 1973, and therefore has a Chief Metropolitan Magistrate. Poisoning is an important public health issue in India and worldwide. The present study is aimed to assess the epidemiological variables of fatal poisonings in Kanpur. Methods: All medico legal autopsies of the city were conducted in the GSVM Medical College mortuary, Kanpur. During the study period, 582 cases of fatal poisoning were autopsied. Only autopsies with confirmed diagnosis of poisoning were included in this prospective study. Results: A total of 7648 medico legal autopsies were performed at the aforementioned centre. Poisoning deaths comprised 582 cases (7.6%) of the total autopsies conducted during the study period. Conclusions: Suicidal poisoning is accountable for majority of poisoning deaths in India. Societies at large owe a collective responsibility to this manner of death and mere condemnation or sympathy is not sufficient to curb these avoidable deaths.